A Review of O'Rourke and Williamson's Globalization and History: The Evolution of a Nineteenth Century Atlantic Economy - Harley, C. Knick (Journal of Economic Literature, 2000)
Much of the comparative economic history of the nineteenth century focuses on the spread of the Industrial Revolution from Britain. Incomes converged, in this view, as the transfer of superior technology raised incomes in the periphery. In Globalization and History, Kevin O'Rourke and Jeffrey Williamson challenge this technological approach, arguing that neoclassical effects of trade and factor supply changes provide more insight. Increased trade, stimulated by falling transportation costs, and factor movements caused prices of locally scarce factors to fall and promoted factor price convergence.